Expression and Role of PIWI Proteins and piRNAs in Reproduction of Water Buffalo (Bubalus bubalis, Linn.) - Hufana, Rocelle Joy C.; D. Canare, Perry Lorraine; Abella, Evaristo A.; Duran, Peregrino G.; Kumar, Rakesh; Hufana-Duran, Danilda (Journal of Buffalo Science, 2022)
High-fertile and productive dairy animals are important to satisfy the growing population's demand. Sire fertility is one of the essential factors that regulate the overall pregnancy rate of dairy herds. However, sire fertility varies from 10 to 90%, suggesting that male fertility largely accounts for varying fertility levels across the herd. Sub-fertile bulls and females should be identified and discarded promptly to improve the dairy herd's productivity. The most dominant factors implicated in culling are poor semen quality, poor semen freezability (<35% post-thaw motility), and poor libido for the bulls and hard breeders for females that cause huge economic loss to the raisers. Understanding the basic mechanism of male and female fertility has undergone tremendous change in recent times owing to the advancement of molecular tools judging the essential molecules responsible for fertility. Presently, a new molecular niche has surfaced in testes, strongly influencing the fertilization potential of spermatozoa. Over the last decade, there has arrived a conclusion that out of several factors, piRNA and PIWI proteins are largely implicated in regulating the vital aspects of fertility and embryogenesis. While this development is advancing in other animals, very limited information is available on PIWI protein and piRNAs in large animals. Except for a few sporadic information on PIWI protein in cattle, very limited information is available on piRNAs and PIWI protein in regulation with buffalo bull fertility and growth of embryos of buffaloes, posting a huge demand for research.